PEMANFAATAN MEDIA PUZZLE BERBASIS PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Pramiswari, Elok Dara; Ambarwati, Adna Arum; Suastika, I Ketut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by observations of students at SDN Tanjungrejo 2 Malang class 5B which are known that many students still get low learning outcomes with the KKTP stipulation of 80. The form of this research is classroom action research conducted at SDN Tanjungrejo 2 Malang in semester of the 2024/2025 academic year and takes from February to April 2025. The subjects of this study were 28 students of class 5B, consisting of 15 male and 13 female students. The purpose of this study is to improve the learning outcomes of IPAS in class 5B students of SDN Tanjungrejo 2 Malang by utilizing puzzle media based on the culturally responsive teaching approach. The results of the study show that using the culturally responsive teaching approach and puzzle media has been proven to significantly improve student learning outcomes and is effective of being recommended as an alternative to active and contextual learning at the elementary school level.